Estructura y electrificación de un lavadero de vehículos en la ciudad de Cartagena de Indias Colombia. - Bernate Izquierdo, Carlos Andrés (Universidad Antonio Nariño, 2022)
The of this proyec is to design the low voltaje electrical installation of a carwash at the city Cartagena. The design include calculating the electrical loads, selecting the materials, sizing the cables, the Transformers and electrical protections in order to meet with client specificiations (Cointracar), to satisfy whit the RETIE regulations and AFINIA, which is the entity that give the conformity and permission to connect to the national electrical network.